Minimally Invasive Surgical Pulmonary Embolectomy: A Potential Alternative to Conventional Sternotomy. Issue 6 (November 2017) - Pasrija, Chetan; Shah, Aakash; Sultanik, Elliot; Rouse, Michael; Ghoreishi, Mehrdad; Bittle, Gregory J.; Boulos, Francesca; Griffith, Bartley P.; Kon, Zachary N.
Abstract : Objective: Surgical pulmonary embolectomy has gained increasing popularity over the past decade with multiple series reporting excellent outcomes in the treatment of submassive pulmonary embolism. However, a significant barrier to the broader adoption of surgical pulmonary embolectomy remains the large incision and long recovery after a full sternotomy. We report the safety and efficacy of using a minimally invasive approach to surgical pulmonary embolectomy. Methods: All consecutive patients undergoing surgical pulmonary embolectomy for a submassive pulmonary embolism (2015–2017) were reviewed. Patients were stratified as conventional or minimally invasive. The minimally invasive approach included a 5- to 7-cm skin incision with upper hemisternotomy to the third intercostal space. The primary outcomes were in-hospital and 90-day survival. Results: Thirty patients (conventional = 20, minimally invasive = 10) were identified. Operative time was similar between the two groups, but cardiopulmonary bypass time was significantly longer in the minimally invasive group (58 vs 94 minutes, P = 0.04). While ventilator time and intensive care unit length of stay were similar between groups, hospital length of stay was 4.5 days shorter in the minimally invasive group, and there was a trend toward less blood product use. In-hospital and 90-day survival was 100%. Within the minimally invasive cohort, median right ventricular dysfunction at discharge was none-mild and no patient experienced postoperative renal failure, deep sternal wound infection, sepsis, or stroke. Conclusions: Minimally invasive surgical pulmonary embolectomy appears to be a feasible approach in the treatment of patients with a submassive pulmonary embolism. A larger, prospective analysis comparing this modality with conventional surgical pulmonary embolectomy may be warranted.